An Empirical Comparison of Alternative Models of the Short-Term Interest Rate. - Chan, K C (Journal of Finance, 1992)
The authors estimate and compare a variety of continuous-time models of the short-term riskless rate using the Generalized Method of Moments. The authors find that the most successful models in capturing the dynamics of the short-term interest rate are those that allow the volatility of interest rate changes to be highly sensitive to the level of the riskless rate. A number of well-known models perform poorly in the comparisons because of their implicit restrictions on term structure volatility. They show that these results have important implications for the use of different term structure models in valuing interest rate contingent claims and in hedging interest rate risk. Coauthors are Andrew Karolyi, Francis A. Longstaff, and Anthony B. Sanders.